2019
DOI: 10.1111/jam.14459
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Bacillus velezensis HC6: production of three kinds of lipopeptides and biocontrol potential in maize

Abstract: Aims: To study the antimicrobial agents of the Bacillus velezensis strain HC6 and assess the application potential of B. velezensis HC6 in maize. Methods and Results: We applied a dual culture technique to test the antimicrobial activity of B. velezensis HC6 against bacteria and fungi of common contaminated crops. Bacillus velezensis HC6 showed antagonistic action on pathogenic fungi, including Aspergillus and Fusarium, as well as pathogenic bacteria (especially Listeria monocytogenes). When applied in maize, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 47 publications
7
48
0
Order By: Relevance
“…B. velezensis is a new type of biocontrol factor with inhibitory ability against a broad spectrum of microbial pathogens and plant growth promoting activity [63]. It produces various antifungal and antibacterial metabolites including β-1,3-1,4-glucanase, lipopeptides (iturin, fengycin and surfactin), polyketides (macrolactin, bacillaene and difficidin or oxydifficidin) and peptides (plantazolicin, amylocyclicin and bacilysin) [64][65][66][67]. It is reported that lipopeptides produced by B. velezensis are the major contributor to inhibiting pathogenic fungi, such as F. oxysporum, C. gloeosporioides and so on [27,68].…”
Section: Discussionmentioning
confidence: 99%
“…B. velezensis is a new type of biocontrol factor with inhibitory ability against a broad spectrum of microbial pathogens and plant growth promoting activity [63]. It produces various antifungal and antibacterial metabolites including β-1,3-1,4-glucanase, lipopeptides (iturin, fengycin and surfactin), polyketides (macrolactin, bacillaene and difficidin or oxydifficidin) and peptides (plantazolicin, amylocyclicin and bacilysin) [64][65][66][67]. It is reported that lipopeptides produced by B. velezensis are the major contributor to inhibiting pathogenic fungi, such as F. oxysporum, C. gloeosporioides and so on [27,68].…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic activity against the pathogens Monilinia fructicola [ 61 ] and B. cinerea (60%) reached maximum levels of > 80% and 60%, respectively, mainly due to the large amount of lipopeptides produced (10 g/L) [ 67 ]. Many studies of olive, tomato, corn, peanut, pepper, maize and rice crop yields have also described the biocontrol activity of B. velezensis strains against phytopathogens such as Verticillium dahliae , Fusarium graminerarum , Sclerotium rolfsii , Phytophthora and B. cinerea [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Our results are in line with the findings of Lee et al (2006) [ 75 ] who investigated the effect of radicular applications of B. subtilis WXCDD105 on B. cinerea in tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…The versatility of HR-MS (especially hybrid HR-MS) is reflected in increased selectivity by eliminating potential interferences originating from the matrix with remarkably similar mass-to-charge ratio (m/z) as of the measured analytes, but with a different structure. Glycopeptides [20][21][22] Oxazolidinones [23,24] Ansamycins [25,26] Quinolones [27,28] Streptogramins [29,30] Lipopeptides [31,32] Antibiotic Resistance [33,34] Table 1.…”
Section: Clinical Applications 21 Analysis Of Antibioticsmentioning
confidence: 99%